TREN EKSPOR KOPI TIMOR LESTE KE INDONESIA : TREN EKSPOR KOPI TIMOR LESTE KE INDONESIA - Martins, Elezito; Lestari, Retna Dewi; Rahyunanto, Setyo (Journal Science Innovation and Technology (SINTECH), 2025)
This study aims to analyze trends in Timor-Leste's coffee exports to Indonesia over the past five years (2020-2025) and the factors influencing them. Timor-Leste, as an agricultural country, makes coffee its primary non-oil and gas export commodity. Timor-Leste's Arabica coffee is known for its high quality and has been exported to various countries, including Indonesia, but with significant fluctuations. This study used quantitative and qualitative methods with secondary data from various sources, including the Ministeriu Agrikultura e Pescas (MAP), the Ministry of Industry of Timor-Leste, and UN Comtrade. Data was analyzed to identify trends in export value and factors such as export volume, export prices, and trade policies. The results show that Timor-Leste's coffee exports to Indonesia have fluctuated, influenced by internal and external factors. Driving factors include geographic proximity, coffee's image as a premium product, and the increasing demand for specialty coffee in Indonesia. Barriers include logistics costs, small production scale, and lack of promotion. This study concludes that despite significant potential, Timor-Leste's coffee exports to Indonesia are not yet optimal. It is recommended that the Timor-Leste government establish national quality standards, increase farmer capacity, and establish trade partnerships with roasters in Indonesia. Promotion and branding also need to be improved to strengthen the position of Timor-Leste coffee in the Indonesian market. This research provides theoretical and practical contributions to agribusiness development and international trade, particularly in the context of developing countries.